2002
DOI: 10.1017/s1357729800052796
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of carcass lean content by real-time ultrasound in Pietrain and negative stress Pietrain

Abstract: lean proportion was higher in homozygote TT than homozygote CC and heterozygote CT individuals ( P < 0·05). Gilts had more lean meat than barrows ( P < 0·05). The correlation between the lean meat proportion and ultrasound backfat thickness (UBFT) or ultrasound longissimus muscle depth (ULMD) respectively was moderate.The prediction of lean meat proportion using UBFT, ULMD and ULMA gave an R 2 which varied from 0·35 to 0·79. Real-time ultrasound is a tool that could potentially be used to predict the compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…BW7.5, AGD7.5, BF7.5 and LD7.5 of CC pigs were higher than these of CT pigs while LM7.5 was similar. This result was consistent with reports of many authors (Sanchez et al 2003;Merour et al 2009) whereas others (Youssao et al 2002a;Luc et al 2008) concluded that the halothane genotype does not affect growth performance. BF5.5 and LD5.5 of females were higher than those of males.…”
Section: Production Performancesupporting
confidence: 92%
See 4 more Smart Citations
“…BW7.5, AGD7.5, BF7.5 and LD7.5 of CC pigs were higher than these of CT pigs while LM7.5 was similar. This result was consistent with reports of many authors (Sanchez et al 2003;Merour et al 2009) whereas others (Youssao et al 2002a;Luc et al 2008) concluded that the halothane genotype does not affect growth performance. BF5.5 and LD5.5 of females were higher than those of males.…”
Section: Production Performancesupporting
confidence: 92%
“…This was the main reason explaining why LM7.5 of males was higher than that of females. The study of Youssao et al (2002a) in Belgium, and Luc et al (2008) in Vietnam also confirmed that females had more fat than males.…”
Section: Production Performancementioning
confidence: 70%
See 3 more Smart Citations